INTEGRATED BIOREMEDIATION STRATEGIES FOR HEAVY METAL CONTAMINATION IN INDUSTRIAL WASTEWATER USING GENETICALLY ENGINEERED MICROBIAL CONSORTIA - Achmad Agus Salim; Han Jiwon; Seo Jiwon (Yayasan Adra Karima Hubbi, 2026)
Industrial activities generate heavy metal waste that challenges conventional methods due to their high cost and low efficiency. This study aims to evaluate the effectiveness of an integrated bioremediation strategy using a genetically engineered microbial consortium in removing heavy metal contaminants while simultaneously improving reactor stability, biosafety, and environmental sustainability. Using a mixed-methods sequential explanatory design, this study tested 420 industrial wastewater samples and 180 laboratory- and pilot-scale bioreactors. The bioreactors represented three treatments: the conventional method, the natural microbial consortium, and the genetically engineered microbial consortium. Quantitative analysis involved descriptive statistics, structural equation modeling (SEM), hierarchical regression, and mediation-moderation analysis. Qualitative data from expert interviews, operational observations, biosafety assessments, and regulatory documents were analyzed thematically. The results demonstrated that the genetically engineered microbial consortium significantly improved heavy metal removal efficiency, microbial viability, metabolic stability, biosorption capacity, reactor performance, and environmental sustainability. Microbial viability was found to partially mediate the relationship between genetic engineering and treatment efficiency, while reactor optimization strengthened the influence of metabolic stability on remediation performance. In conclusion, the sustainability of industrial wastewater treatment depends on the coordinated integration of microbial genetic engineering, ecological cooperation, reactor optimization, biosafety management, and environmental governance to provide a scalable bioremediation framework.